2016
DOI: 10.2105/ajph.2016.303397
|View full text |Cite
|
Sign up to set email alerts
|

US Food Industry Progress During the National Salt Reduction Initiative: 2009–2014

Abstract: The US Food and Drug Administration's proposed voluntary targets will be an important step in achieving more substantial sodium reductions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 9 publications
4
58
0
Order By: Relevance
“…In relation to the NSRI, by 2014, data from US packaged foods showed that 43% of food categories had significantly reduced sodium, but most categories did not meet 2014 NSRI targets, and US dietary data suggest that sodium intake has not substantially declined (2,20). With implementation of Health Canada benchmarks, significant sodium reductions were observed in w16% of processed food categories by 2013, and further data on sodium intake reduction are not available to our knowledge (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to the NSRI, by 2014, data from US packaged foods showed that 43% of food categories had significantly reduced sodium, but most categories did not meet 2014 NSRI targets, and US dietary data suggest that sodium intake has not substantially declined (2,20). With implementation of Health Canada benchmarks, significant sodium reductions were observed in w16% of processed food categories by 2013, and further data on sodium intake reduction are not available to our knowledge (21).…”
Section: Discussionmentioning
confidence: 99%
“…Both standards were based on the sodium content of foods that are produced by major food manufacturers. Although declines occurred in the sodium content of some US and Canadian commercially processed foods after the publication of these standards, sodium standards were not met for all food categories, and the potential impact on the change in sodium intake has been unclear (2,(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…NSRI is the first organized public health effort in the United States to engage industry in reducing sodium in the food supply. A coalition of more than 100 local public health agencies and national health organizations led by the New York City Department of Health and Mental Hygiene encouraged food companies to meet NSRI sodium reduction targets (5). The NSRI database was designed to assess sodium levels and other information listed on nutrition labels of US processed foods over time.…”
Section: Methodsmentioning
confidence: 99%
“…The remaining 54 food categories span the following broader food categories or metacategories: bakery products; cereal and other grain products; meats; dairy products and substitutes; fats and oils; sauces, dips, gravies, and condiments; snacks; soups; potatoes; mixed dishes; vegetables; legumes; canned fish; and nut butters. A detailed description of the NSRI processed food categories is published elsewhere (5). …”
Section: Methodsmentioning
confidence: 99%
“…20 Recent results demonstrate modest success in decreasing sodium content in these products, as well as decreases of salesweighted mean sodium density (by 6.8%, P<.001) in nearly half of all food categories (43%). 21 Companies continue commitments to reducing sodium in foods; PepsiCo recently announced it will have at least threequarters of its global foods portfolio volume restricted to ≤1.3mg of sodium/calorie. 22 In 2016, the US Food and Drug Administration announced a voluntary sodium reduction strategy for the food industry.…”
Section: Dietary Sources Of Sodium Nhanes 2011-12 -Firestone Et Almentioning
confidence: 99%